Within-Family Environment and Cross-Fostering Stress Affect Behavior and Physiology in Wild Cavies (Cavia aperea) - Kraus, Sabine; Trillmich, Fritz; Guenther, Anja (Frontiers in Psychology, 2020)
Stability of personality traits is well documented for a wide variety of animals. However, previous results also suggest that behavioural phenotypes are plastic during early ontogeny and can be adaptively shaped to the social environment. In cavies (Cavia aperea), it has already been documented that the size at birth relative to siblings (size rank) greatly influences various behavioural and physiological traits that last at least until independence. The aim of the current study was (1) to investigate if behavioural and physiological differences between pups of the same litter persist until after independence and influence development long-lasting, (2) to determine the potential plasticity in response to changes in the early within-family environment by cross-fostering pups either to the same, a lower, or a higher size rank in a foster-family. We measured three behavioural traits (number of interactions with a novel object, distance moved in an open field, struggle docility) and two physiological traits (resting metabolic rate and basal cortisol levels). We predicted that cross-fostering into a litter where pups occupy the same size rank would not change the expression of traits. Cross-fostering to a different size rank should not influence the expression of traits if repeatability measures indicate low plasticity. Alternatively, if the traits are plastic, animals should adjust trait expression to fit with the size rank occupied in the foster litter. Initial differences in struggle docility, distance moved in an open field and in baseline cortisol concentration between pups of different size-ranks did not remain stable beyond independence. In addition, we found remarkable plasticity of the measured traits in response to cross-fostering to the same, a smaller or larger size-rank, suggesting that differences between pups are more the result of social constraints leading to adaptive shaping of individual phenotypes within a family. We also found a significant influence of the cross-fostering procedure itself. Cross-fostered individuals were less bold, grew slower and showed elevated resting metabolic rates. This finding suggests a cautious interpretation of previous cross-fostering studies and stresses the need for proper control groups to reliably separate the effect of cross-fostering per se from those induced by an experimental treatment.